Mamushi bites in a kidney transplant recipient. Issue 4 (1st May 2022) - Ando, Tadasuke; Nakashima, Syunsuke; Abe, Satoki; Watanabe, Dai; Iwasaki, Kazunori; Shinohara, Mayuka; Kai, Tomoki; Hata, Shinro; Shibuya, Tadamasa; Shin, Toshitaka
Abstract : Introduction: Mamushi bites are the most common venomous snakebites in Japan. The clinical course of a common mamushi bite is known, and its alarming complication and cause of death are acute renal failure due to the venom. However, reports of mamushi bites in kidney transplant recipients are lacking, and the clinical course is unknown. Case presentation: A 66‐year‐old man who was bitten by a mamushi 3 years after kidney transplantation. Similar to the course of a typical mamushi bite, his severity gradually worsened to its peak 3 days after the bite, after which he turned lightly. A sufficient amount of infusion and continued immunosuppressive drugs were used to avoid acute renal failure. Conclusion: Even if the mamushi bite occurs in a kidney transplant recipient, the course and management may be the same as usual by continuing the immunosuppressive drugs and a sufficient amount of infusion.